IMMUNOEXPRESSION OF TWIST IN DIFFERENT MORPHOLOGICAL VARIANTS OF AMELOBLASTOMAS - Khalil, Eyyaz; Rehman, Abdur; Ahmed, Fiaz (Journal of Ayub Medical College Abbottabad, 2015)
Background: Ameloblastoma is the most common and a clinically significant odontogenic tumour. The diagnosis and sub classification of ameloblastoma have been traditionally relied on histological assessment, but it is still a subject of debate. The aim of this study was to evaluate the immuno-expression of Twist in various subtypes of ameloblastomas and their co-relation with various histological variants. Methods: This cross-sectional study was conducted in the Department of Pathology, Post Graduate Medical Institute, Lahore between June to December 2013. Thirty cases of various types of Ameloblastomas were included in this study. Histological sub-classification of the tumours was performed based on WHO classification. Twist expression of these tumours was estimated by immunohistochemistry, performed on paraffin sections. Results: Out of these thirty cases, 22 (73%) were newly diagnosed typical solid/multicystic intraosseous ameloblastoma, 2 (7%) cases belonged to recurrent ameloblastoma, and 3 (10%) each were diagnosed as peripheral/extraosseous ameloblastoma and ameloblastic carcinoma. On histopathological sub-classification of the newly diagnosed solid ameloblastoma, 8 cases were diagnosed as follicular ameloblastoma in which 3 cases (37.5%) were negatively stained, 4 cases (50%) were mild positive and 1 case (12.5%) was moderate positive with Twist immunostaining. Out of 5 cases of plexiform ameloblastoma 3 cases (60%) were mild positive. Out of 4 cases of acanthomatous ameloblastoma 2 (50%) were moderate positive and 2 cases (50%) were strong positive. All granular cell ameloblastoma stained positive. The only case of desmoplastic ameloblastoma was moderately positive. Both the cases of recurrent ameloblastoma were strongly positive. All 3 cases of peripheral ameloblastoma stained negatively. All ameloblastic carcinoma were strongly positive. Conclusion: Twist immunohistochemical analysis can be used as an adjuvant to H&E histopathological findings for proper categorization and grading of ameloblastoma especially in the clinically aggressive tumours. Keywords: Ameloblastoma, Twist, gene,immunoexpression